Protesilaos, two ways - Stewart, Andrew (Journal of Greek Archaeology, 2022)
Two monuments to the hero Protesilaos, both nautical but each unique in its own way, pose some intriguing methodological problems. Of contested date and authorship, extant only in Roman-period reproductions (in different media), but linked by a common theme, they engage both texts and contexts in different ways. They illustrate not only the richness and creativity of the ancient material and textual record, and the indispensability of the ancient reproductions, but also the methodological flexibility advised to tackle such material in general.